2022
DOI: 10.3390/horticulturae8121220
|View full text |Cite
|
Sign up to set email alerts
|

Could an Early Treatment with GA and BA Impact Prolonged Cold Storage and Shelf Life of Apricot?

Abstract: Application of plant growth regulators (PGRs) in apricot orchards is a common practice with a goal of improving yield and/or quality of fruits at harvest. However, the question of whether such treatment alters postharvest properties is seldom answered. The effects of an early application of PGRs on postharvest changes on apricots were investigated on cultivar NS-4, grown on Myrobalan rootstock with blackthorn interstock in a 5-year-old orchard. PGR treatments included 50 and 100 ppm of benzyladenine (BA) and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 29 publications
0
2
0
Order By: Relevance
“…In another study in Bergarouge apricots, TC concentration increased during CS at 1 • C for 14 days and then decreased at day 21, while when fruit were subjected to SL, TC values remained at constant levels until day 4 and then decreased on day 8 [42]. Also, Milović et al [41] reported an increase in TC concentration in NS-4 apricots during CS at 1 • C for 21 days and after 3 days of SL. Ruiz et al [26] reported that TC values ranged between 1.3 and 38.5 mg 100 g −1 FW and observed a significant relationship between flesh color and TC concentration in 37 apricot cultivars, proposing that the use of color parameter values, particularly h • , can lead to the prediction of TC content of apricot cultivars.…”
Section: Total Carotenes and Individual Carotenoid Compoundsmentioning
confidence: 92%
See 1 more Smart Citation
“…In another study in Bergarouge apricots, TC concentration increased during CS at 1 • C for 14 days and then decreased at day 21, while when fruit were subjected to SL, TC values remained at constant levels until day 4 and then decreased on day 8 [42]. Also, Milović et al [41] reported an increase in TC concentration in NS-4 apricots during CS at 1 • C for 21 days and after 3 days of SL. Ruiz et al [26] reported that TC values ranged between 1.3 and 38.5 mg 100 g −1 FW and observed a significant relationship between flesh color and TC concentration in 37 apricot cultivars, proposing that the use of color parameter values, particularly h • , can lead to the prediction of TC content of apricot cultivars.…”
Section: Total Carotenes and Individual Carotenoid Compoundsmentioning
confidence: 92%
“…However, Orange Rubis apricots exhibited significantly lower values in the determined variables of TP, TF, and TAC compared to Orange Red fruit when subjected to SL right after harvest. In another study on NS-4 apricots stored at 1 • C for 21 days, the levels of TP and TF were found at almost stable levels but decreased after SL at 24 • C for 3 days [41]. Contrarily, Ezzat et al [42] reported that the levels of TP and TAC, evaluated using FRAP assay, decreased during CS at 1 • C for up to 21 days and during SL at 25 • C for up to 8 days.…”
Section: Total Antioxidants and Total Antioxidant Capacitymentioning
confidence: 93%